Relationship between the perception of classroom learning environment and student academic emotions - Lira Fessia Damaianti; Risda Awaliya; Ifa Hanifah Misbach (Jurnal Konseling dan Pendidikan, 2019)
Perception of classroom environment and academic emotions have an important role in the educational context. Both have a relationship that can not be separated from each other. This study aims to examine the correlation between perception of classroom learning environment and academic emotions in junior high school students in the city of Bandung. Using the quasy experimental method with a quantitative approach with a correlational design with a sample of 81 respondents aged 12-14 years who were selected using a purposive sampling technique. The instruments in this study consisted of academic emotions questionnaire (AEQ) and my class inventory (MCI) that had been translated into Indonesian. Data analysis was performed using the Pearson product moment. The results showed a positive correlation between the dimensions of competitiveness with negative academic emotions and a negative correlation between the dimensions of satisfaction with negative academic emotions in junior high school students in the city of Bandung.